Charge! - Lam, Choon Khee (2013)
CHARGE! is a 2D animation about a troop of robots obeying every single order given by their commander, all except one with the courage to disobey the order. This animation is influenced by the soviet posters in the 1930s where these posters often delivered Communist Party’s slogans to the masses to fight for freedom and justice. The concept and objective of this animation is to depict the characteristic and style of the Soviet poster to my film. This film sends an important message to the audience, that is do what is right and not what is told.